Karl Marx dan konsep perjuangan kelas sosial - Indriaty Ismail,; Mohd Zuhaili Kamal Basir, (Universiti Kebangsaan Malaysia, 2012)
This article explores the history of the renowned world economic and political reformist, Karl Marx with a special focus on the social class concept. It also discusses to what extent that the Marx’s concept of social class struggle is capable to provide a way out to the proletariats, to free themselves from the chains of cruelty, violence and alienation in the capitalist system. Our main focal point is to scrutinize the relationship between the concepts of social class struggle and the need for a social revolution as a catalyst for the formation of a classless society. Along the way, we studied and analyzed the documents produced on the primary sources covering major works of Marx and the secondary sources consisting reviews of the Marx’s class concept. As a result, we found out that Marx’s concept of class fight is competent to represent the oppressed group to battle for their freedom rights. The Proletariat dictatorship attitude was used as their main shield to face the threat of the capitalist class. Marx’s ultimate success is realized through a burst of ideas and beliefs that supports the ideas of egalitarian Communism although many contradictions arise between the ideas of Marx and the 20th centuries Communism when they are translated into practice.